Contrast Induced Nephropathy - Nurul R Ningrum; Yoga Yuniadi (The Indonesian Heart Association, 2009)
Incidens of contrast induced nephropathy (CIN) ranging from 0 to 100% in retrospective cohort studies depend on its definition, method of investigation and subject characterization. In National Cardiovasculars Center Harapan Kita, CIN incidence after percutaneous coronary intervention was 25% using definition of 0.5 mg/dl increase of serum creatinine. Clinical spectrum of CIN is widely variably from only creatinine serum increment to acute renal failure.Pathogenesis of CIN is related to hemodynamic compromize of renal blood flow and direct toxic effect of contrast media. Some factors were identified as CIN risk factors such as previous renal status, diabetes mellitus, hidration status, contrast volume and osmality. Score system has been developed to predict CIN risk after percutaneous coronary intervention. The Society of Cardiovascular Angiography and Intervention (SCAI) proposed guideline to prevent CIN after percutaneous coronary interventions.